2016
DOI: 10.1016/j.jtrangeo.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Built environment, peak hours and route choice efficiency: An investigation of commuting efficiency using GPS data

Abstract: Commuting efficiency measures the impact of commuting on urban spatial and social environments. Urban policies aim to reduce commuting distances and improve commuting efficiency by supporting mixed land-use and job-housing balance. Many studies have addressed these issues by examining excess commuting at the aggregate level, and most aggregated measurements of excess commuting are based on home-to-work commuting flows between zones. However, residents' travel behaviour does not consist solely of rational attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Another clear finding is that the temporal patterns of clusters of travel flows were significantly related to spatial factors, which is consistent with the findings of most studies that human movement is regular, both spatially and temporally [4,7,35]. This finding makes it possible to manage residents' travel routes based on their routine travel to parks.…”
Section: Bundles Of Trips To Parkssupporting
confidence: 85%
See 2 more Smart Citations
“…Another clear finding is that the temporal patterns of clusters of travel flows were significantly related to spatial factors, which is consistent with the findings of most studies that human movement is regular, both spatially and temporally [4,7,35]. This finding makes it possible to manage residents' travel routes based on their routine travel to parks.…”
Section: Bundles Of Trips To Parkssupporting
confidence: 85%
“…However, sometimes park visitors may not actually follow the shortest path [21]. For example, travelers often take detours to avoid traffic jams, or because they have incomplete information about transport options and conditions [35]. Some authors have also found that visitors select travel routes based on travel time rather than the shortest path [21,36].…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Fridman et al [27] used styles, applications, web browsing, and GPS positioning to realize the related technologies of active authentication on mobile devices. Based on the survey of GPS-assisted travel in Beijing suburbs, Ta et al [28] studied the related technologies of personal commuting efficiency according to the difference in commuting distance and route selection efficiency between the morning and evening peak traffic hours. Aliprantis et al [29] described a concept with image identification and matching from the Europeana platform, which can link the LOD cloud from cultural institutes around Europe and mobile augmented reality applications for cultural heritage without accurate geo-based locations.…”
Section: Literature Review and Development Technologiesmentioning
confidence: 99%
“…Previous regulations about commercial activities such as shopping centres, retail trade, restaurants and offices in residential areas were relaxed to accommodate the pressures for these amenities, resulting in a mixed land use. While such mixed land-use is encouraged to reduce traffic (Ta et al 2016), residential location choice in Dhaka is often based on school ing of children, and not the commute distances or local amenities (Choudhury and Ayaz 2016), which calls into question the advantages of mixed land use. Especially, the proliferation of unplanned shops and shopping centres throughout the city is thought to be a major contributor to congestion.…”
Section: Background On Dhakamentioning
confidence: 99%